Antibacterial Activity of Steroids Isolated from the Madagascar Marine Sponge Biemna laboutei: Δ7 Steroids as New Potential Agents Against Pathogenic Bacteria - Ralambondrahety, Rahanira; Couzinet-Mossion, Aurélie; Rabesaotra, Vony; Andriambeloson, Onja; Barnathan, Gilles; Rakotovao, Marcelle; Wielgosz-Collin, Gaëtane (Natural Products Journal, The, 2021)
Background: Nowadays, the efficiency of antibiotics is endangered by the development of resistant bacterial strains. Consequently, novel bioactive agents are intensively searched. Marine sponges are well-known for being major sources of bioactive compounds, including unusual sterols. Until now, among sterols, noteworthy antibacterial activity has been reported exclusively for Δ5 sterols. Objectives: This study aims to describe the steroid composition of the marine sponge Biemna laboutei collected in the North coast of Madagascar, and the antibacterial activity of steroid mixture against human pathogenic strains. Methods: Sponge was extracted in CHCl3/MeOH. Free steroids were separated from other lipids by column chromatography with dichloromethane as specific eluent. Free sterols/steroids and sterol acetates were analysed by gas chromatography coupled with mass spectrometry. Antibacterial activity of steroid fractions was assessed for eight strains using agar diffusion with cellulose disks. Results: Neutral lipids were the major lipid class (79.1% of total lipids). The dichloromethane eluted fraction contained only free steroids giving rise to the identification of eleven compounds. These components presented exclusively Δ7 unsaturation, including lathosterol as the major one (38.4%) and four 3-oxo-steroids (11.8%). The steroid fraction of B. laboutei has exhibited inhibitory activity against pathogenic strains but more particularly against gram(+) Bacillus cereus (MIC of 12.5 μg/mL) and Staphylococcus aureus (MIC of 25 μg/mL) strains. This latter bacterium causes several illnesses, some of those strains being antibiotic-resistant and this becomes a worldwide health problem. Conclusion: This is the first report for an antibacterial activity of a mixture of Δ7 steroids against a resistant strain of S. aureus to many antibiotics.
Keywords: Marine invertebrates